Mezzanine finance and corporate restructuring - Tetřevová, Liběna (Univerzita Pardubice, 2009)
The article deals with the problems of mezzanine finance in relation to corporate restructuring. The term mezzanine finance is used as a term for hybrid forms of financing that combine elements of debt and equity financing. Mezzanine finance represents an alternative form of financing restructuring activities of companies. The corporate restructuring means the whole reorganization of company, regeneration of all entrepreneurial parts. Corporate restructuring is based on realization of suitable restructuring measures in production, business, organization, information, personnel or financial and property spheres. The attention is paid to basic concept of mezzanine finance and corporate restructuring and to their mutual relations.
Keywords: corporate restructuring; NR restructuring; PR restructuring; mezzanine finance; mezzanine capital